TElmisartan in the management of abDominal aortic aneurYsm (TEDY): The study protocol for a randomized controlled trial - Morris, D.; Cunningham, M.; Ahimastos, A.; Kingwell, B.; Pappas, E.; Bourke, M.; Reid, Christopher; Stijnen, T.; Dalman, R.; Aalami, O.; Lindeman, J.; Norman, P.; et al. (BioMed Central Ltd., 2015)
Background: Experimental studies suggest that angiotensin II plays a central role in the pathogenesis of abdominal aortic aneurysm. This trial aims to evaluate the efficacy of the angiotensin receptor blocker telmisartan in limiting the progression of abdominal aortic aneurysm. Methods/Design: Telmisartan in the management of abdominal aortic aneurysm (TEDY) is a multicentre, parallel-design, randomised, double-blind, placebo-controlled trial with an intention-to-treat analysis. We aim to randomly assign 300 participants with small abdominal aortic aneurysm to either 40 mg of telmisartan or identical placebo and follow patients over 2 years. The primary endpoint will be abdominal aortic aneurysm growth as measured by 1) maximum infra-renal aortic volume on computed tomographic angiography, 2) maximum orthogonal diameter on computed tomographic angiography, and 3) maximum diameter on ultrasound. Secondary endpoints include change in resting brachial blood pressure, abdominal aortic aneurysm biomarker profile and health-related quality of life. TEDY is an international collaboration conducted from major vascular centres in Australia, the United States and the Netherlands. Discussion: Currently, no medication has been convincingly demonstrated to limit abdominal aortic aneurysm progression. TEDY will examine the potential of a promising treatment strategy for patients with small abdominal aortic aneurysms. Trial registration: Australian and Leiden study centres: Australian New Zealand Clinical Trials Registry ACTRN12611000931976, registered on 30 August 2011; Stanford study centre: clinicaltrials.gov NCT01683084, registered on 5 September 2012.